Peran PR dalam Membangun Citra Melalui Instagram (Studi Pada Humas DPRD Kota Bogor) - Christina Jocelyn; Yugih Setyanto (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
The development of information technology and social media provides great opportunities for public relations (PR) to support government institutions in increasing transparency and building a positive image in the eyes of the public. As an important part of strategic communication, Bogor City DPRD Public Relations uses Instagram social media to establish harmonious relationships with the community. This research aims to examine the role of Public Relations of the Bogor City DPRD in building the image of the institution through the Instagram platform. The method used is descriptive qualitative with an in-depth interview approach to related sources. The research results show that the Instagram account @dprd.kotabogor is managed effectively to convey information on DPRD activities and programs transparently. This account is also used to increase public participation and strengthen the institution's positive image. As a communication liaison, Bogor City DPRD Public Relations contributes significantly in building good relationships between institutions and the community through targeted communication strategies. This research provides insight for other government institutions regarding optimizing social media as an effective means of public communication, especially in the city of Bogor. Perkembangan teknologi informasi dan media sosial memberikan peluang besar bagi public relations (PR) untuk mendukung lembaga pemerintahan dalam meningkatkan transparansi dan membangun citra positif di mata publik. Sebagai bagian penting dari komunikasi strategis, Humas DPRD Kota Bogor memanfaatkan media sosial Instagram untuk menjalin hubungan yang harmonis dengan masyarakat. Penelitian ini bertujuan untuk mengkaji peran Humas DPRD Kota Bogor dalam membangun citra lembaga melalui platform Instagram. Metode yang digunakan adalah deskriptif kualitatif dengan pendekatan wawancara mendalam terhadap narasumber terkait. Hasil penelitian menunjukkan bahwa akun Instagram @dprd.kotabogor dikelola secara maksimal untuk menyampaikan informasi kegiatan dan program DPRD secara transparan. Akun ini juga digunakan untuk meningkatkan partisipasi publik dan memperkuat citra positif lembaga. Sebagai penghubung komunikasi, Humas DPRD Kota Bogor berkontribusi signifikan dalam membangun hubungan yang baik antara lembaga dan masyarakat melalui strategi komunikasi yang terarah. Penelitian ini memberikan wawasan bagi lembaga pemerintahan lainnya mengenai optimalisasi media sosial sebagai sarana komunikasi publik yang optimal, khususnya di Kota Bogor.